The effect of low advanced glycation end product diet on bone health and cardio-metabolic parameters in overweight and obese postmenopausal women: study protocol for a randomised controlled trial (AGEs study) - Jamka, Małgorzata; Kurek, Szymon; Miśkiewicz-Chotnicka, Anna; Krzyżanowska-Jankowska, Patrycja; Walkowiak, Marek; Bęben, Małgorzata; Wichłacz-Trojanowska, Natalia; Brylak, Jan; Makarewicz-Bukowska, Aleksandra; Chrobot, Maria; Jaworska, Natalia; Popek, Joanna; et al. (Journal of Medical Science, 2024)
Advanced glycation end products (AGEs) have been suggested to play an important role in osteoporosis. However, no randomised controlled trial has investigated the effect of a diet with low AGEs on densitometric parameters. This study will evaluate the effect of a 12-month low AGEs diet on bone health and cardio-metabolic parameters in postmenopausal overweight and obese women. In total, 80 subjects will be included in the study and randomly divided into two groups: low AGEs diet and standard AGEs diet for 12 months. The mineral density and content will be measured at the lumbar spine, femoral neck, and total body during the pre- and post-intervention period. Selected markers of bone formation and resorption will be assessed. Anthropometric parameters and body composition will be evaluated and markers of glucose, insulin, lipid metabolism, inflammatory and endothelial parameters will be measured. Adherence to the diet will be monitored using dietary records.
Keywords: postmenopause; overnutrition; metabolic diseases; bone density; nutrition therapy